Effectiveness of synbiotics as laxative agent for constipation in children - Hannah Hannah; M. Juffrie; S. Yati Soenarto (Indonesian Pediatric Society, 2008)
Background Constipation in children can cause serious problems.Laxative is needed for the management of constipation. Orallaxative has been used frequently, even though a safe oral laxativeagents for children is limited. Prebiotic and probiotic have alreadybeen proven to have laxative effect in constipation in children andadults. The effectiveness of these agents as a laxative has not beenproven yet.Objective To evaluate the effectiveness of laxative synbiotic inconstipation in children compared to that of fiber foods.Methods A randomized double blind controlled trial wasconducted on children aged 6 months-14 years old who sufferedfrom functional constipation at Dr. Sardjito Hospital, Dr. SoeradjiTirtonegoro Hospital, and Wates District Hospital from April2007-October 2007. Randomization was performed by computer. Theoutcome of recovery rate, onset therapy and side effects wereevaluated after seven days of intervention.Results Forty-three children were included in this study, but only41 could be analyzed. Subject characteristics in both groups werecomparable except for maternal educational level. The mainoutcome (recovery rate) was assessed by intention to treat principle.Compared with fiber foods, synbiotic increased the recovery ratewith RR 2.14 (95%CI 1.14; 4.02) and NNT 2.9 (95%CI 2; 15),whereas its therapeutic onset was 15 hours faster than that of fiberfoods. No important side effects were found in both groups.Conclusions Synbiotic is safe and effective in increasing therecovery rate of functional constipation with faster therapeuticonset than that of fiber foods.